2022
DOI: 10.1093/trstmh/trac074
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological aspects of severe acute respiratory infection: before and during the first year of the COVID-19 pandemic in Brazil

Abstract: Background Widespread respiratory infections with high morbidity rates caused by respiratory viruses represent a significant global public health problem. Our objective was to describe cases and deaths from severe acute respiratory infection (SARI) in Brazil over the past 8 y as well as changes in the distribution and risk of illness and death from SARI before and in the first year of the coronavirus disease 2019 (COVID-19) pandemic (FYP). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The pandemic revealed that SARI mortality was no longer solely attributed to influenza, but also heavily impacted by COVID-19. Countries like Brazil and India experienced a dramatic rise in SARI cases and deaths during the pandemic period [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic revealed that SARI mortality was no longer solely attributed to influenza, but also heavily impacted by COVID-19. Countries like Brazil and India experienced a dramatic rise in SARI cases and deaths during the pandemic period [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%